2013
DOI: 10.1108/08876041311309225
|View full text |Cite
|
Sign up to set email alerts
|

Configural algorithms of patient satisfaction, participation in diagnostics, and treatment decisions ' influences on hospital loyalty

Abstract: Purpose -This empirical study aims to explore sufficiency conditions for patient loyalty to a hospital. Design/methodology/approach -The study collected 645 self-administered questionnaires from patients in a major medical center in Taiwan and applied fuzzy set qualitative comparative analysis (fs/QCA) to explore the sufficiency conditions for patient loyalty. Findings -The findings support the conclusion that the three conditions (patient satisfaction, patient participation in the process of diagnosis, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 66 publications
10
122
0
6
Order By: Relevance
“…Unlike traditional statistics which detects patterns of relationships between variables, fs/QCA focuses on examining the configurations of cases that constitute the rows of a data matrix (Chang et al, 2013). This method provides researchers a huge opportunity to explore or re-exam some previously neglected or disproved relationship/arguments.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike traditional statistics which detects patterns of relationships between variables, fs/QCA focuses on examining the configurations of cases that constitute the rows of a data matrix (Chang et al, 2013). This method provides researchers a huge opportunity to explore or re-exam some previously neglected or disproved relationship/arguments.…”
Section: Methodsmentioning
confidence: 99%
“…Anderson et al (1994) additionally called attention to that customer loyalty is resolved to a substantial degree by consumer sa tisfaction. More recently, Chang et al (2013) observed that patients' satisfaction exerts a positive influence on gaining patients loyalty for concerned hospitals. Further, in the hospitality industry, Kim et al (2015) empirically found customer satisfaction and loyalty to be strongly associated.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%
“…as an example for conducting GT using quantitative data (Chang, Tseng, & Woodside, 2013;Wu, Yeh, & Woodside, Wu et al, 2014). QCA is not suggested as "the approach" to be followed when conducting GT using quantitative data, but rather as an example.…”
Section: Conducting Gt With Quantitative Datamentioning
confidence: 99%